Strong constraints on the b → sγ photon polarisation from B0 → K*0e+e− decays; Journal of High Energy Physics; Vol. 2020, iss. 12 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Adeva B. Bernardo; Adinolfi M. Marco; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2020, 2020)
Title screen